The design and implementation of mobile communication base station inspection system based on Web technology - Yang, Kun; Cheng, Bo; Peng, Yong (2012 2nd International Conference on Computer Science and Network Technology, 2012)
The Mobile Communication Base Station Inspection is one type of basic work to ensure safe operation of the base station equipment. By using the mobile application development technology, we propose an effective solution to improve the work efficiency and business processing speed. In this paper, we design and implement a Mobile Communication Base Station Inspection System by integrating Mobile application development technology and Web technology. In the System we implement four modules: Login, Setting, Task Management and Base Station Inspection. With the mobile client application developed on mobile terminals platforms, inspection staffs could keep abreast of the state or process of inspection work anytime.